Insights into local atomic structure of Fe alloyed ZnS nano crystals: Correlation with structural, optical, magnetic and photocatalyst properties - Ghorai S.; Patra N.; Pal A.; Bhattacharyya D.; Jha S.N.; Ray B.; Chatterjee S.; Ghosh A.K. (My University, 2025)
The effect of Fe dopant on the structural, optical, magnetic properties and local atomic structure of aqueous synthesis derived Zn1-xFexS (0 ≤ x ≤ 0.06) nanocrystals have systematically investigated. The crystallite structure and crystallite size have been estimated by X-ray diffraction with Rietveld refinement and transmission electron microscopy. Scanning electron microscopy demonstrates the sphalerite morphology. Raman spectroscopy has been employed to observe the effect in crystalline quality and local defects on the host lattice. Defect formation due to Fe dopant on ZnS nanocrystals has been demonstrated by photoluminescence spectroscopy. The local electronic structure of Zn and Fe sites are investigated thoroughly by synchrotron based X-ray absorption spectroscopy. Significant fraction of Fe–Fe data of extended X-ray absorption fine structure suggests that interstitial Fe sites are present. The sphalerite ZnS and Fe doped ZnS (x = 0, 0.02 and 0.06) showed the photocatalytic activity in methylene blue solution at ambient pressure and temperature on visible and ultraviolet light irradiation. The results illustrate that higher Fe doped ZnS (x = 0.06) photocatalyst with sphalerite morphology has strong photocatalytic activity on ultraviolet irradiation. The temperature dependence magnetization of higher doping concentration (x = 0.06) has been explained with a combined model of spin wave and Curie Weiss fitting. The ferromagnetism at low temperature has been studied with bound magnetic polaron model. © 2019